Oocytes with a dark zona pellucida demonstrate lower fertilization, implantation and clinical pregnancy rates in IVF/ICSI cycles. - Wei Shi; Bo Xu; Li-Min Wu; Ren-Tao Jin; Hong-Bing Luan; Li-Hua Luo; Qing Zhu; Lars Johansson; Yu-Sheng Liu; Xian-Hong Tong (PLoS ONE)
The morphological assessment of oocytes is important for embryologists to identify and select MII oocytes in IVF/ICSI cycles. Dysmorphism of oocytes decreases viability and the developmental potential of oocytes as well as the clinical pregnancy rate. Several reports have suggested that oocytes with a dark zona pellucida (DZP) correlate with the outcome of IVF treatment. However, the effect of DZP on oocyte quality, fertilization, implantation, and pregnancy outcome were not investigated in detail. In this study, a retrospective analysis was performed in 268 infertile patients with fallopian tube obstruction and/or male factor infertility. In 204 of these patients, all oocytes were surrounded by a normal zona pellucida (NZP, control group), whereas 46 patients were found to have part of their retrieved oocytes enclosed by NZP and the other by DZP (Group A). In addition, all oocytes enclosed by DZP were retrieved from 18 patients (Group B). No differences were detected between the control and group A. Compared to the control group, the rates of fertilization, good quality embryos, implantation and clinical pregnancy were significantly decreased in group B. Furthermore, mitochondria in oocytes with a DZP in both of the two study groups (A and B) were severely damaged with several ultrastructural alterations, which were associated with an increased density of the zona pellucida and vacuolization. Briefly, oocytes with a DZP affected the clinical outcome in IVF/ICSI cycles and appeared to contain more ultrastructural alterations. Thus, DZP could be used as a potential selective marker for embryologists during daily laboratory work.